PC.44 Improved cognitive ability in preterm infants: The impact of a sepsis reduction care bundle. (9th June 2014) - Davis, JW; Jary, S; Cairns, PA; Harding, D; Luyt, K
Abstract : Background: Very low birth weight infants (VLBW; <1500 g) with late onset sepsis have an increased risk of neurodisability. Care bundles to reduce blood stream infections in NICU have been shown to be effective. Objective: To determine if the implementation of a sepsis reduction care bundle was associated with improvement in neurodevelopmental outcomes in VLBW infants. Methods: A sepsis improvement care bundle was implemented in a tertiary level NICU between 2006–2007. Mortality and neurological morbidity rates were compared for the pre-intervention (January 2001–December 2007) and post-intervention (July 2008–December 2012) periods. The highest risk VLBW infants (<30 weeks' gestation) had routine neurodevelopmental assessments at 24 months using the Bayley Scales of Infant development (BSID). Moderate cognitive disability was defined as a cognitive/language score below 2SDs. Results: Coagulase Negative Staphylococcus septicaemia rates were 7/1000 care days before implementation of the care bundle and have reduced to an average of 2.8/1000 care days by 2013. In the cohort of VLBW infants there was no significant reduction in mortality rates (66/426(16%) vs. 40/310(13%); p = 0.3). A significant reduction in moderate cognitive disability (16/86(19%) vs. 2/44(5%); p = 0.03) was found after full implementation of the sepsis care bundle. Potentially confounding variables (birth weight and gender) were not different (p > 0.05) in the pre and post intervention cohorts. Conclusions: This is the first description of the long term impact of a sepsis improvement care bundle on neurodevelopmental outcomes in VLBW infants. The improvement seen in cognitive function at 2 years is likely to translate into significantly less long term learning disability.